PENGARUH PROSOCIAL BEHAVIOR, SISTEM PENGENDALIAN INTERNAL, PARTISIPASI MASYARAKAT, KOMITMEN ORGANISASI, DAN KEPEMIMPINAN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Anjar Surdiyani; Baldric Siregar; Frasto Biyanto; Miswanto, Miswanto (Bajang Institute, 2025)
This research aims to test prosocial behavior, internal control system, community participation, organizational commitment, and leadership affect the accountability of village fund management. The population of this research is all village fund managers who are in 11 Village Governments in Panjatan District, Kulon Progo Regency, Special Region of Yogyakarta. The sampling method in this study used the saturated sampling method. The sample of this research is 88 respondents who are village officials involved in managing village funds as described in PERMENDAGRI No. 20 of 2018. The type of data in this study is quantitative data. The source of the data used in this research is primary data using the questionnaire method. The data analysis method used in this research are descriptive statistics, data quality test, and hypothesis testing. The results of this research indicate that prosocial behavior, internal control system, community participation, organizational commitment, and leadership have a significant effect on the accountability of village fund management.